Fibromatous Epulis in a Captive Lion (Panthera leo) - Castro, Márcio B. de; Barbeitas, Mady M.; Borges, Tânia J.; Bonorino, Rafael P.; Ramos, Roberta R.; Szabó, Matias P. J. (Brazilian Journal of Veterinary Pathology, 2011)
An epulis in the oral cavity of an aged captive lion in Brasilia, Brazil, is reported. Oral inspection of the animal revealed a pale blunt and irregular multilobulated mass involving the upper left caninum tooth. Microscopic features of the mass included a fibrous stroma (mesenchyme) interspaced with a few blood vessels, suggesting a periodontal ligament origin. The dense collagen fiber background had a moderate cellularity composed of regularly orientated fibroblasts and it surrounded foci of osteoid or mineralized material. Mild overlying gingival epithelial hyperplasia with some irregular cellular cords was also observed. Based on the location of the lesion as well as the gross and microscopic features, the lesion was classified as fibromatous epulis and is believed to be the first report in this species.